Originality Within Or/and Outside the Lexicographic Tradition: Comparison of Uskuffs Dictionary to Ibrahim Šahidi’s Dictionary (Prilozi za orijentalnu filologiju, 2017)
Rad se bavi pitanjem originalnosti u leksikografiji opÄ‡enito a na primjeru komparacije rjeÄnika MakbÃ»l-i Vir;/'Mehmeda Uskufije Bosnevije i rjeÄnika Tuhfe-i ÅžÃ¢hidÃ® Ibrahima Å ahidije. U radu se analizira struktura i sadrÅ¾aj obaju tjeÄnika, odabir leksike u njima, rima, metar i povezanost reÄenica i/ili fraza unutar cjeline djela. Usporedba Uskufijinog rjeÄnika sa rjeÄnikom Tuhfe-i ÅžÃ¢hidÄ± Ibrahima Å ahidije pokazuje Uskufijinu originalnost u odabiru metra, leksike u bosanskom, sadrÅ¾aja i veliÄine poglavlja, kao i originalnost u nizanju leksema u inkoativnim frazama na poÄetku poglavlja i sadrÅ¾aju finitnih fraza/ reÄenica pri kraju poglavlja. OpÄ‡enito gledajuÄ‡i, sam Uskufijin odabir stihovane forme mulemme za pisanje bosansko-turskog rjeÄnika i danas Uskufiju Äini originalnim u historiji juÅ¾noslavenske leksikografije. Osim toga, Uskufija je bosansku leksikografiju pribliÅ¾io tada veÄ‡ vrlo razvijenoj leksikografskoj tradiciji na orijentalnim jezicima. Na osnovu komparacije Uskufijina i Å ahidijina rjeÄnika doÅ¡li smo do zakljuÄka da je u rjeÄnicima moguÄ‡e pronalaziti elemente â€œoriginalnostiâ€ i razliÄitosti, makar oni pripadali i istoj leksikografskoj tradiciji, Å¡koli ili pravcu. Takva vrsta razliÄitosti i â€œoriginalnostiâ€ jedan je od faktora razvitka leksikografije uopÄ‡e.-------------------------------------------------Originality within or/and outside the lexicographic tradition: comparison of uskuffs dictionary to Ibrahim Å ahidiâ€™s dictionaryThe paper deals with the issue of originality in lexicography generally, using the example of comparison of the dictionary MakbCd-i 'Arif by Mehmed Uskufi Bosnevi and the dictionary Tuhfe-i ÅžÃ¢hidÃ® by Ä°brahim Å ahidi. The paper analyses the structure and contents of both dictionaries, the selection of the Iexis, rhymes, metre, and sentence coherence in them and/or the phrases in the works as a whole. The comparison of Uskufiâ€™s dictionary to the dictionary Tuhfe-i ÅžÃ¢hidÃ® by Ä°brahim Å ahidi shows Uskufiâ€™s originality in the selection of the metre, the lexis in Bosnian, the contents and length of the chapters, as well as the originality in stringing lexemes in inchoative phrases at the beginning of the chapters and content of the finite phrases/sentences by the end of the chapter. Generally speaking, Uskufiâ€™s selection itseÃ®f of the mÃ¼lemma verse form to write the Bosnian-Turkish dictionary makes Uskufi original stili today in the history of South-Slavic lexicography. Additionally, Uskufi brought the Bosnian lexicography nearer to the already very developed lexicographic tradition in Oriental languages of the time. On the basis of comparison of Uskufiâ€™s dictionary to Sahidiâ€™s dictionary, we have come to a conclusion that it is possible to find elements of â€œoriginalityâ€ and dissimilarity in dictionaries, even if they belong to the same lexicographic tradition, school or direction. Such a kind of dissimilarity and â€œoriginalityâ€ is one of the factors of lexicography development generally.